Basic and clinical role of vitamins in epilepsy - Raha Zalkhani; AhmadAli Moazedi (Journal of Research in Applied and Basic Medical Sciences, 2020)
Background & Aims: Epilepsy is a brain disorder which affects about 50 million people worldwide. Good diet is an essential measure to controlling seizure attacks. Since some combination therapy can reduce epileptogenesis, therefore this review summarizes the available evidences about the application of vitamins in animal models and humans for understanding what specific combinations of antiepileptic drugs and vitamins are likely to be effective for epilepsy therapy. Material and methods: In this review, electronic databases including PubMed and Google Scholar were searched for monotherapy and polytherapy by vitamins. Results: Administration of vit A inhibits development of seizures and lethality in animal models. Also vitamins B1, B6 and B12 pre-treatment might lead to a protective effect against degenerative cellular in mice. In addition use of low dose of sodium valproate with vitamins C or E increase the anticonvulsant activity of the drug in mice. Moreover, Vitamin D enhances antiepileptic effects of lamotrigine, phenytoin and valproate in animal's models. Vitamin E has an anticonvulsant effect in ferrous chloride seizures, hyperbaric oxygen seizures as well as penicillin-induced seizures in contrast kindling, maximal electroshock and kainite models. Some researches demonstrated that vitamins D and B as adjunctive therapy in epileptic patient can relieve seizures. A clinical data have shown beneficial effects of vitamin E in raising total antioxidant capacity, catalase, and glutathione in patients with uncontrolled epilepsy. Only few clinical studies exist to support the efficacy of the vitamin A and K in epilepsy. Conclusion: However vitamin therapy is not a substitute for antiepileptic drugs but add on therapy by them may relieve drugs- induced deficiencies as well as more researches are needed to evaluate the effectiveness of vitamins in epileptic humans.